Victimization, Offending, and Expectations for Future Success among High-Risk Youth. Issue 6 (3rd June 2021) - Hinton, Marissa E.; Tillyer, Marie Skubak; Tillyer, Rob
ABSTRACT: The present study examined consequences of a well-established criminological phenomenon, the victim-offender overlap, and how its prevalence and effects are influenced by the inclusion of indirect victimization, an often overlooked form of victimization. Specifically, we examined how experiencing and/or witnessing victimization, engaging in delinquent behavior, and the combination of these experiences (i.e., the victim-offender overlap) influence an adolescent's expectations for achievement in work, family, and law-abiding behavior in adulthood. Using data from Pathways to Desistance, a longitudinal study of adolescent offenders, we distinguished between direct and indirect victimization, as well as proximal and distal victimization and offending experiences, to assess their independent and collective effects. Findings demonstrate the importance of considering the consequences of indirect victimization, the combination of victimization and offending experiences influence how adolescents perceive their futures, and more distal experiences with crime are not predictive of expectations for success in adulthood.